What structural and cultural organizational characteristics affect flexible work environments? Evidence from the 2017 and 2022 Kessler Foundation National Employment & Disability Survey: Supervisor perspectives. - Kim, Hyun Ju; Jablonski, Erica; Brucker, Debra L.; Chen, Ada; O'Neill, John; Houtenville, Andrew J.; Katz, Elaine E. (Journal of Vocational Rehabilitation, 2024)
Background: As workplace flexibility can promote employment for people with disabilities, people with disabilities need information about the characteristics of organizations that are more likely to provide this environment. Objective: Using the 2017 and 2022 Kessler Foundation National Employment & Disability Survey: Supervisor Perspectives, we examine organizational characteristics associated with the flexible work accommodations of working from home, flexible work schedules, and job sharing, prior to and after the COVID-19 pandemic. Methods: We employ a linear probability model to investigate the impact of the COVID-19 pandemic on the provision of flexible workplaces and explore structural (industry, sector, and size) as well as cultural factors (central accommodation fund and upper management commitments) that are related to the flexible workplace practices. Results: The pandemic increased flexible workplace practices. Different organizational structural and cultural characteristics are noted as correlates to providing greater workplace flexibility. Conclusion: Our findings can inform job seekers with disabilities to identify organizations that are more likely to offer flexibility. In addition, this information can be useful to vocational rehabilitation professionals in supporting positive employment outcomes for people with disabilities. Employers can also use our findings to guide their diversity, equity, and inclusion efforts.